If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4x + 1) + -1(-3x + -5) = -3 Reorder the terms: -1(1 + 4x) + -1(-3x + -5) = -3 (1 * -1 + 4x * -1) + -1(-3x + -5) = -3 (-1 + -4x) + -1(-3x + -5) = -3 Reorder the terms: -1 + -4x + -1(-5 + -3x) = -3 -1 + -4x + (-5 * -1 + -3x * -1) = -3 -1 + -4x + (5 + 3x) = -3 Reorder the terms: -1 + 5 + -4x + 3x = -3 Combine like terms: -1 + 5 = 4 4 + -4x + 3x = -3 Combine like terms: -4x + 3x = -1x 4 + -1x = -3 Solving 4 + -1x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = -3 + -4 -1x = -3 + -4 Combine like terms: -3 + -4 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| -(4x+1)-(-3y-5)=-3 | | 8n^2+n=-11 | | 0.5x-3=17 | | 5(x^2-3)=5 | | 8y+8=64 | | 6r^2-9=3 | | G-5=-9 | | 2+-6=y | | a^2-10=50 | | 1x+5=13 | | -10x^2=-360 | | x-8.1=-6.9 | | x+33=24 | | n^2-3=46 | | 9y-1=80 | | 10x-2=-72 | | 10x+15=95 | | 5x+32=x | | n^2=46 | | 5+2h=20 | | -72-3(-9-4)=3(-9-4)+6 | | 5y-5=10 | | 8x-3(x-4)=3(x-4)+6 | | 2y-7=9 | | y=4x+3whatisy | | 3x-2(2+5)=2(x+3)-8 | | 10x+14=34 | | -5x+5=10 | | y=3+4x | | -10x+6=26 | | -x+4y=3 | | 5v-20=25 |